MANAGING HOTELS IN A SUSTAINABLE WAY - Marie Cazaban Loustaunau (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
As global tourist arrival numbers continue to increase demand and supply trends in regard to sustainable business practices are fundamental. Hotel owners and operators must adapt to these changes in order to satisfy demand and remain attractive to investors as well as operationally feasible and profitable. This article is review some actions that are done in some hotel and could be generalized to every hotel with a little effort. It shows is a surface examination of the benefits of sustainable business practices. To write this article, I used several tools. First, I used the materials from my first year of master’s degree. Then, I read scientific articles and thesis related to the topic. Finally, over my course about green tourism in Bali, my classmates and I had the opportunity to visit the Conrad Bali in Nusa Dua. We had the chance to exchange with Mr. Stephane Roubin, director of operations. He shared his awe-inspiring career history as well as answer all of our question about Conrad Bali and the commitments of the hotel to developed itself in a sustainable way. This research and analysis point out one very important thing: green tourism is not a trend but the only way to make our planet survive. Each little action made by tourism and hospitality industry’s actors is a step to carry on welcoming tourist from all around the world and make them enjoy the beauty of each destination. In Bali, huge efforts in term of ocean pollution and recycling especially must be done.